2017 40th International Conference on Telecommunications and Signal Processing (TSP) 2017
DOI: 10.1109/tsp.2017.8076102
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Based terahertz antennas for area-constrained applications

Abstract: Abstract-Graphene is enabling a plethora of applications in a wide range of fields due to its unique electrical, mechanical, and optical properties. In the realm of wireless communications, graphene shows great promise for the implementation of miniaturized and tunable antennas in the terahertz band. These unique advantages open the door to disruptive wireless applications in highly integrated scenarios where conventional communications means cannot be employed. In this paper, recent advances in plasmonic grap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Figure 7 shows the resonance characteristics of the antenna as a function of the chemical potential. The increase of chemical potential leads to a significant shift of the resonant frequency and to an enhancement of the antenna response without changes in the radiation pattern [105].…”
Section: Design Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 7 shows the resonance characteristics of the antenna as a function of the chemical potential. The increase of chemical potential leads to a significant shift of the resonant frequency and to an enhancement of the antenna response without changes in the radiation pattern [105].…”
Section: Design Issuesmentioning
confidence: 99%
“…Figure 7 shows the resonance characteristics of the antenna as a function of the chemical potential. The increase of chemical potential leads to a significant shift of the resonant frequency and to an enhancement of the antenna response without changes in the radiation pattern [105]. Absorption enhancement based on metal nanoparticle dispersive properties of metal nanoantenna structures is also a critical design issue that needs also consideration.…”
Section: Design Issuesmentioning
confidence: 99%
“…Nanoantennas operating in THz band are of great importance in everyday life due to their numerous utilizations in the various photonics fields. Initially, graphene-based antennas were hypothetically studied, while recent studies by Sergai and colleagues [102] demonstrated graphene as the radiating element in a stack graphene-based dipole antenna that resonates at terahertz frequency band, as depicted in Figure 3a. The dipole antenna is designed by employing graphene sheet stacks on low index material (LIM; i.e., quartz) substrate with the dielectric constant ε r = 3.8.…”
Section: Graphene Resonant Terahertz Antennasmentioning
confidence: 99%
“…(a) Graphene stack dipole antenna on low index material (LIM); (b) input impedance and resonance frequency as a function of dipole arm length, where the frequency shifts to lower end as the length increases; (c) comparison of graphene radiator with gold, as gold radiator resonates at a higher frequency than graphene; and (d,e) behavior of conductivity with respect to changes in chemical potential and relaxation time. © IEEE 2017, Reprinted with permission from[102].…”
mentioning
confidence: 99%
“…The infinite graphene film can be modeled by an equivalent surface, which can be calculated by means of the Kubo formalism . The surface conductivity can be represented in a local, Drude‐like form σ()ω=2e2πhkBTln[]2cosh[]μc2kBTiω+iτ1 where T is room temperature ( T = 300 K), transport relaxation time τ is a typical value ( τ = 1 ps), μ c is the chemical potential.…”
Section: Model Of Graphene Antennamentioning
confidence: 99%